Reconstruction of the Spanish money supply, 1492–1810 - Chen, Yao (2021)
How did the Spanish money supply evolve in the aftermath of the discovery of large amounts of precious metals in Spanish America? We synthesize the available data on the mining of precious metals and their international flow to estimate the money supply for Spain from 1492 to 1810. Our estimate suggests that the Spanish money supply increased more than ten-fold. Viewed through the equation of exchange this money supply increase can account for most of the price level rise in early modern Spain.